(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Long-term antiretroviral drug toxicity may exacerbate the impact of HAART-Cyperus esculentus (C. esculentus) interactions on testicular function in HIV-infected individuals. This study examined the ability of C. esculentus plants to treat testicular dysfunction, which is thought to be a probable side effect of antiretroviral toxicity. Adult Wistar male rats weighing 90–110 g were divided into six groups and administered the prescribed treatments. In addition to testicular histology and stereological parameters, testosterone levels, follicle-stimulating hormone levels, antioxidant markers, malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione levels were also evaluated. The adverse consequences of highly active antiretroviral therapy (HAART) include considerable loss of germ cells, enlargement of the tubular lumen, widening of interstitial gaps, and severe hypocellularity. Compared to the other treatment groups, MDA levels dramatically increased, whereas GSH and antioxidant enzyme (SOD) levels significantly decreased. Testicular architecture was largely conserved after treatment with C. esculentus, with a notable increase in the cellular densities of germinal and interstitial cells and a notable decrease in the tubular lumen. Vacuolation, architectural malformations, and hypoplastic changes were reduced. Significant improvements were also observed in C. esculentus in terms of elevated antioxidant SOD and GSH levels and decreased MDA levels. C. esculentus reduced architectural distortions and testicular dysfunction caused by HAART, and improved testicular morphology. Further exploration of these pathways is required.